Personal Income Taxes and the January Effect: Small Firm Stock Returns Before the War Revenue Act of 1917: A Note - SCHULTZ, PAUL (Journal of Finance, 1985)
ABSTRACT This paper tests the tax explanation of the January effect by examining small firm stock returns before the War Revenue Act of 1917. No evidence of a turn‐of‐the‐year effect is found. This paper also extends previous authors' work on the subject to 1918–29. A January effect is found during that period.